Efforts to Improve Thematic Learning Achievement Material Theme 7 Leadership Subtheme 3 Let's Lead by Applying the Learning by Doing Learning Model to Grade Vi Students of Madrasah Ibtidaiyah Negeri 3 East Jakarta Academic Year 2018/2019 - Jamaluddin Jamaluddin (International Journal Labs, 2023)
This research is based on the following problems: (a) Does learning by doing affect Thematic learning achievement in Class VI Students? (b) How high is the level of mastery of Thematic subject matter with the application of learning by doing learning methods to Class VI Students? The objectives of this study are: (a) To uncover the flow of learning by doing on Thematic learning achievements in Class VI Students. (b) Want to know how far the understanding and mastery of Thematic subjects after the application of learning by doing to Grade VI Students This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was Class VI students. The data obtained are in the form of formative test results and, observation sheets for teaching and learning activities. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (66%), cycle II (83%), cycle III (100%). The conclusion of this study is that the learning-by-doing method can have a positive effect on the learning motivation of Class VI students, and this learning model can be used as a thematic alternative